Effects of Online Live Pilates Training during the COVID-19 Pandemic on Body Composition, Cardiovascular Function, and Physical Fitness in Sedentary Middle-aged Obese Women - Jung-Heon Choi; Ko-Eun Choi; Man-Gyoon Lee (Korea Institute of Sport Science, 2022)
PURPOSE This study aimed to investigate how a 10-week online live Pilates training held during the COVID-19 pandemic affected body composition, cardiovascular function, and physical fitness in sedentary middle-aged obese women. METHODS Thirty obese women, aged 30 to 49 years (BMI : 25kg/m2 or more; waist circumference: 85cm or more) who were leading a sedentary lifestyle for more than 8 hours a day were assigned to one of two groups-that is, the Pilates training group (TR) and the control group (CON). Four participants were dropped from the study during the intervention period. Participants in the TR group (n=13) performed online live mat Pilates exercises (3 sessions per week; 60 minutes per session for 10 weeks, whereas participants in the CON group (n=13) were asked to maintain their normal lifestyles during the same intervention period. Independent variables related to body composition, cardiovascular function, venous function in the lower body, physical fitness, and 1-RM (repetition maximum) were measured at pre-test and post-test, and data were compared between the two groups and between the two tests. RESULTS 1) Regarding body composition, body weight, body mass index, fat mass, and waist circumference decreased significantly in the TR group. 2) Regarding cardiovascular function, stroke volume and cardiac output increased significantly in the TR group, and total peripheral resistance decreased significantly in the TR group. 3) Regarding venous function in the lower body, blood flow velocity and blood flow volume of the parenchyma area increased significantly in the TR group. 4) Regarding physical fitness, cardiorespiratory endurance, muscular endurance, flexibility, and balance improved significantly in the TR group. 5) 1RM of biceps curl, lat pull-down, leg curl, and leg extension increased significantly in the TR group. CONCLUSIONS It was concluded that the 10-week online live Pilates training had positive effects on the body composition, cardiovascular function, venous function in the lower body, and physical fitness of middle-aged obese women leading sedentary lifestyles.